2012
DOI: 10.3926/ic.345
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quantity and quality of education on innovation

Abstract: ResumenObjeto: El presente trabajo trata de determinar, empíricamente y para una muestra amplia de países, qué tipo de variables educativas pueden explicar mejor los procesos de innovación tecnológica, aproximados a través del número de patentes per cápita. Para ello, utilizamos un modelo que explica la capacidad innovadora de los países utilizando seis variables educativas: dos variables de cantidad -años medios de estudio, totales y universitariosy cuatro de calidad -basadas en los resultados obtenidos en di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Nevertheless, we looked in a different direction to understand the relationship between ICT use at school and students' outcomes, hypothesizing that the countries' stock of human capital might be a positive externality in the relationship between students' outcomes and ICT use. We confirmed our hypothesis, according to previous arguments, that supported the role of the stock of human capital as a catalyst of new technologies [15,16,[36][37][38], which have the capacity to create and improve pedagogical and institutional educational environments [39][40][41][42] and to engage better teachers [45,46]. Regardless of the subject assessed and the human capital indicator considered, average years of schooling (BL) or average years of schooling weighted by the Mincerian rates of return to education (PWT), the moderator-effect of the stock of human capital turned the negative relationship between students' outcomes and ICT use at school into a positive one.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, we looked in a different direction to understand the relationship between ICT use at school and students' outcomes, hypothesizing that the countries' stock of human capital might be a positive externality in the relationship between students' outcomes and ICT use. We confirmed our hypothesis, according to previous arguments, that supported the role of the stock of human capital as a catalyst of new technologies [15,16,[36][37][38], which have the capacity to create and improve pedagogical and institutional educational environments [39][40][41][42] and to engage better teachers [45,46]. Regardless of the subject assessed and the human capital indicator considered, average years of schooling (BL) or average years of schooling weighted by the Mincerian rates of return to education (PWT), the moderator-effect of the stock of human capital turned the negative relationship between students' outcomes and ICT use at school into a positive one.…”
Section: Discussionsupporting
confidence: 90%
“…The assimilation and effective use of technology. We consider the stock of human capital as a catalyst of new technologies: the process of adoption of new technologies is strongly influenced by the human capital stock, by reducing new technologies' learning costs and accelerating their adoption [15,[36][37][38].…”
Section: The Role Of Human Capitalmentioning
confidence: 99%
“…Human capital is measured as the average years of schooling of males above 15 years old [47,48]. A substantial number of studies have found a significant positive association between this measure of human capital and economic growth in both developed and developing countries [49][50][51], through a direct effect in the production function and an indirect one through innovation, imitation and the quality of institutions [50,[52][53][54]. Measures of education quality, based on internationally comparable test scores, have shown an important explanatory power for growth.…”
Section: The Baseline Model and Datamentioning
confidence: 99%